2012
DOI: 10.1016/j.intimp.2011.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the NF-κB signaling pathway by the curcumin analog, 3,5-Bis(2-pyridinylmethylidene)-4-piperidone (EF31): Anti-inflammatory and anti-cancer properties

Abstract: Nuclear factor kappa B (NF-κB) is a key signaling molecule in the elaboration of the inflammatory response. Data indicate that curcumin, a natural ingredient of the curry spice turmeric, acts as a NF-κB inhibitor and exhibits both anti-inflammatory and anti-cancer properties. Curcumin analogues with enhanced activity on the NF-κB and other inflammatory signaling pathways have been developed including the synthetic monoketone compound termed 3,5-Bis(2-fluorobenzylidene)-4-piperidone (EF24). 3,5-Bis(2-pyridinylm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
125
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(138 citation statements)
references
References 38 publications
2
125
0
3
Order By: Relevance
“…For example, chemical modification of the curcumin molecule led to more potent inhibitors curcuminoids of NF-κB activity than curcumin, while exhibiting both antiinflammatory and anticancer activities [100,101].…”
Section: Fig 7 Level Of Mda In Plasma Of Control (C) Rats and Tumormentioning
confidence: 99%
“…For example, chemical modification of the curcumin molecule led to more potent inhibitors curcuminoids of NF-κB activity than curcumin, while exhibiting both antiinflammatory and anticancer activities [100,101].…”
Section: Fig 7 Level Of Mda In Plasma Of Control (C) Rats and Tumormentioning
confidence: 99%
“…51 In parallel, EF31 increases basal levels of MAPK transcription factor-DNA binding in mouse RAW264.7 macrophages. 9 To elucidate a global view of the anticancer/cytocidal actions of these compounds, we sought information regarding their drug targets by using microarrays, and examined cellular localization of EF24 and the activity of two key transcription factors, AP-1 and NF-κB, essential for cell survival and death.…”
Section: Figmentioning
confidence: 99%
“…5 We have found that four MACs with a common mechanism of action, including EF24, EF25, EF31 and UBS109, may be clinically useful. [6][7][8][9][10][11][12] Here, we summarize tumorigenic actions of the subset of MACs considered in this work. EF24, EF25, EF31 and UBS109 inhibit a wide variety of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Madrigal and colleagues (2001) have demonstrated that inhibition of NF-κB translocation in the rat brain cortex decreased iNOS activity and expression following acute stress. Natural compounds such as curcumin, α-tocopherol, and resveratrol have also been shown to inhibit NF-κB activation and the associated neuroinflammatory response including both cytokines and iNOS induction (Suzuki and Packer, 1993;Lu et al, 2010;Olivera et al, 2012). Another important inflammatory signalling cascade involves cyclooxygenase-2 (COX-2), a constitutively expressed enzyme in the brain that converts arachidonic acid into prostaglandin.…”
Section: Introductionmentioning
confidence: 99%